Survey of hospital doctors' attitudes and knowledge of oral conditions in older patients - Morgan, R (BMJ Group, 2001)
The study was designed to assess the views and knowledge of hospital doctors in general and geriatric medicine on oral health in older people. Eighty two doctors in general and geriatric medicine at two hospitals were shown 12 colour slides of oral mucosal conditions and asked to give a diagnosis for each slide and complete a questionnaire. Completed questionnaires with the answers to the coloured slides were returned completed by 70( )doctors. The majority of doctors (84%) felt it was important to examine older patients' mouths, however only 19% (χ(2) p=0.0001) routinely do so. If asked to prescribe nystatin by the nursing staff, 30% said they would do so without examining the mouth itself. Only 9% of doctors knew that wearing dentures was a specific risk factor for oral candidiasis (χ(2) p=0.001). Altogether 56% of doctors did not feel confident in examining the oral cavity and most (77%) did not think they had had sufficient training in this examination. Only two doctors correctly diagnosed all of the slides. An early squamous carcinoma was misdiagnosed by 80% of the doctors (χ(2) p=0.0001). Hospital doctors do not routinely inspect older patients' mouths. Even if shown slides of typical oral mucosal lesions many hospital doctors are unable to diagnose them. Issues on training need to be addressed. From the patients' point of view a public health campaign is required to educate older people on the need for a regular dental review and be aware that doctors may not be able to diagnose serious oral conditions.